2017
DOI: 10.1002/2016jg003495
|View full text |Cite
|
Sign up to set email alerts
|

High terrestrial carbon load via groundwater to a boreal lake dominated by surface water inflow

Abstract: The input of dissolved organic and inorganic carbon (DOC and DIC) via direct groundwater seepage to boreal lakes is often assumed to be small in noncarbonaceous areas. However, measurements are rare. We estimated the terrestrial load of DOC, DIC, and methane (CH4) to a small boreal lake for the open water period, on the basis of measured concentrations of carbon species in near‐shore groundwater wells and inlet streams, and measured area‐specific discharge. The subcatchment directly draining into the lake via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 66 publications
1
49
0
Order By: Relevance
“…Humic-like DOC is generally derived from the terrestrial environment and is susceptible to within-lake processes and may be rapidly lost from the water column by mineralization, flocculation, or transformation to other DOC by-products [Kothawala et al, 2014]. Flocculation, in particular, is an important transformation process for humic-like DOC components as it has been shown that in lakes, up to 22% of terrestrially derived DOC can be lost from the water column merely from flocculation and subsequent sedimentation [Einarsdottir et al, 2017;von Wachenfeldt and Tranvik, 2008]. The observed increase in DOC in freshwaters in the present study is probably mostly of terrestrial origin, hence consisting of humic-like components [Kothawala et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Humic-like DOC is generally derived from the terrestrial environment and is susceptible to within-lake processes and may be rapidly lost from the water column by mineralization, flocculation, or transformation to other DOC by-products [Kothawala et al, 2014]. Flocculation, in particular, is an important transformation process for humic-like DOC components as it has been shown that in lakes, up to 22% of terrestrially derived DOC can be lost from the water column merely from flocculation and subsequent sedimentation [Einarsdottir et al, 2017;von Wachenfeldt and Tranvik, 2008]. The observed increase in DOC in freshwaters in the present study is probably mostly of terrestrial origin, hence consisting of humic-like components [Kothawala et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…While in transit, the composition of organic matter can be modified by several processes, including photo‐oxidation, respiration, leaching, flocculation, sorption, and settling (Eckard et al, ; Einarsdottir et al, ; Galy et al, ; Spencer et al, ; von Wachenfeldt & Tranvik, ). Most studies on organic C processing by microbes focused on the dissolved fraction as it is the largest contributor to the organic C pool in inland waters (Thurman, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, important cold‐water fish such as salmon and brown trout thrive in a habitat of combining high DO concentrations and low water temperature (Dillon et al, ; Jiang et al, ), typical for the hypolimnion of natural temperate oligotrophic lakes. Importantly, climate change influences temperate lakes through both air‐water interactions and terrestrial‐aquatic interactions (Buffam et al, ; Cardille et al, ; Cole et al, ; Einarsdottir et al, ). For the latter, the transport of water, carbon, and nutrients from catchments to lakes could change considerably under future climate in temperate regions, which would inevitably affect the water and biogeochemical cycles in small temperate lakes (Anderson et al, ; Catalán et al, ; Couture et al, ; Tanentzap et al, ).…”
Section: Introductionmentioning
confidence: 99%